THE ROLE OF THE FINANCIAL SERVICES AUTHORITY IN FOREIGN INVESTMENT IN ILLEGAL FINANCIAL TECHNOLOGY IN INDONESIA - Agustinli Agustinli (Sean Institute, 2023)
One of the fintech fields most targeted by investors is the type of fintech Peer to Peer (P2P) Lending that provides money loan services. Seeing the magnitude of opportunities in this field, many companies that offer P2P Lending services illegally are called illegal because they are not registered and do not have permission from the OJK. Illegal P2P Lending is very troubling to the community, where the billing system and interest charged to customers who are delinquent in payment bills are very high. Unfortunately, the regulations governing P2P Lending are inadequate, so OJK, as an institution authorized to supervise financial institutions, including online loans, cannot carry out supervision and enforcement optimally. This paper aims to determine the role of OJK in foreign investment in illegal fintech in Indonesia. This writing uses normative juridical research methods where the author will use regulations and legal systems related to the role of OJK in foreign investment in the field of illegal Fintech in Indonesia. OJK has the function of organizing a system of regulation and supervision of all activities in the financial services sector in Indonesia, and has a limited role in foreign investment in the field of illegal P2P lending. Because illegal P2P Lending is considered not the domain of OJK's authority because there is no registered mark and permission from OJK, it is necessary to play a role with other government agencies that are members of SWI to make efforts to stop illegal P2P fintech, which will later be followed up based on the authority of SWI members. OJK can only carry out preventive efforts in the form of socialization accompanied by education and coordinate efforts between institutions in order to accelerate the process of handlers who are members of SWI.